Structural design of buildings : holistic design - Fu, Feng; Richardson, David (Emerald Publishing Limited, 2024)
Structural Design of Buildings: Holistic Design is the essential reference for structural engineers involved in the design of buildings and other structures. It forms part of the Structural Design of Buildings series and introduces the concepts and principles involved in holistic structural design of a building. Broken down into the key areas for understanding and undertaking structural design, and with a fully international approach, this book features coverage of: Soil-structure interaction; Tall buildings; Movement and tolerances; Modular construction; Structural fire engineering design; Structural robustness; Materials science; Seismic design for buildings. The book provides a comprehensive and practical guide to the design of buildings from a structural perspective. It is a timely and essential read for consultants, designers, technicians and contractors tasked with a holistic approach to structural design.
Includes index.
Keywords: Structural design.; Technology & Engineering -- Civil -- General.; Structural engineering.; Civil engineering, surveying and building.; elektronické knihy; electronic books